Multi-Depot General Colored Traveling Salesman Problem with Time Windows in Home Healthcare System: A Medication Delivery Example - Acar, Ilgin; Altin, Islam (International Journal of Industrial Engineering: Theory, Applications and Practice, 2025)
This paper focuses on the problem of medication delivery, specifically addressing meeting the medication demands of patients by different pharmacies. Medication delivery, along with the distribution of vaccines and test kits, is a crucial component of home healthcare services, primarily aiming to serve elderly patients and those with physical or psychological disabilities. A significant aspect of these services is the direct delivery of medications from pharmacies to patients' homes. The importance of home healthcare services has grown, particularly during the pandemic, as many patients faced difficulties accessing both prescribed and over-the-counter medications during lockdowns. The medication delivery problem under consideration is modeled as a Multi-Depot General Colored Traveling Salesman Problem with Time Windows (MD-GCTSP-TW). To solve this problem, a mixed integer mathematical model and a metaheuristic algorithm were designed. The effectiveness of these methods was tested on a variety of test problems, demonstrating the metaheuristic's efficiency through promising results.